Pengaruh Independensi Keahlian Profesi Motivasi Kerja Pengalaman Kerja Dan Tingkat Pendidikan Terhadap Kinerja Pengawas Koperasi - Kodyawati, Putu; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 27 No 2 (2019), 2019)
The purpose of this study was to obtain empirical evidence of the effect of independence, professional expertise, work motivation, work experience and level of education on the performance of cooperative supervisors in Klungkung District. This research was carried out in all cooperatives in Klungkung District. The population is 126 supervisors. The number of samples taken was 66 supervisors with a purposive sampling method. Data collection is done through surveys and questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis it was found that independence, professional expertise, work motivation, work experience and education level simultaneously had a positive effect on supervisor performance. Partially that independence, professional expertise, work motivation, work experience and level of education also influence the performance of supervisors. Keywords: Independence, professional proficiency, motivation